Pediculated Accessory Liver Lobe with Gallbladder in a Preterm with Umbilical Cord Hernia - Martha Georgina Brandtner; Hannah N. Stundner-Ladenhauf; Sara Lapointe-Rohde; Christa Schimke; Dietrich Kluth; Roman Metzger (MDPI AG, 2022)
(1) Background: Accessory liver lobes are a rare finding and only a few case reports of accessory liver lobes in abdominal wall defects have been reported so far. In the case of a congenital wall defect including liver parenchyma, there is still an ongoing debate on the definition of the abdominal wall defect and best care practice. Even though congenital abdominal wall defects are frequently diagnosed in prenatal screenings, controversy on the underlying etiology, embryology and underlying anatomy remains. Prenatal distinction between omphalocele and hernia into the cord cannot always be obtained; however, due to its clinical relevance for postnatal management and counseling of parents, accurate diagnosis is essential. (2) Case Presentation: We describe the uncommon postnatal finding of a pediculated accessory liver lobe with gallbladder in a preterm with umbilical cord hernia, which was prenatally diagnosed as omphalocele. Postnatal examination revealed an amniotic sac with a diameter of six and a small abdominal wall defect of three centimeters in diameter. Postnatal management included resection of the accessory liver lobe and gallbladder and closure of the defect. (3) Results and (4) Conclusions: Throughout the literature, the distinction between umbilical cord hernia and omphalocele has been variable. This has led to confusion and difficulties regarding postnatal treatment options. In order to achieve an accurate prenatal and/or postnatal diagnosis, the morphological differences and clinical manifestation of umbilical cord hernia and omphalocele need to be assessed. Further embryological studies are warranted to understand the underlying embryological pathology of omphalocele and umbilical cord hernia and offer appropriate treatment. In consideration of possibly severe complications in the case of the torsion of a pedunculated accessory liver lobe, we strongly recommend primary removal once pre- or intraoperative identification has been made.